Bridging the Gap: Gene Therapy in a Patient With Spinal Muscular Atrophy Type 1. (22nd November 2022) - Costamagna, Gianluca; Govoni, Alessandra; Wise, Adina; Corti, Stefania
Abstract : Molecular therapies exploit the understanding of pathogenic mechanisms to reconstitute impaired gene function or manipulate flawed RNA expression. These therapies include (1) RNA interference by antisense oligonucleotides, (2) mRNA modification using small molecules, and (3) gene replacement therapy, the viral-mediated intracellular delivery of exogenous nucleic acids to reverse a genetic defect. Several molecular therapies are approved for treating spinal muscular atrophy (SMA), a recessive genetic disorder caused by survival motor neuron ( SMN ) 1 gene alterations. SMA involves degeneration of lower motor neurons, which leads to progressive muscle weakness, hypotonia, and hypotrophy. Onasemnogene abeparvovec is a gene replacement therapy for SMA that uses adeno-associated virus delivery of functional SMN1 cDNA to motor neurons. Two other molecular therapies modulate SMN2 transcription: nusinersen, an antisense oligonucleotide, and risdiplam, a small molecule designed to modify faulty mRNA expression. The most suitable individualized treatment for SMA is not established. Here, we describe remarkable clinical improvement in a 4-month-old patient with SMA type 1 who received onasemnogene abeparvovec therapy. This case represents an explanatory bridge from bench to bedside with regard to therapeutic approaches for genetic disorders in neurology. Knowledge of the detailed mechanisms underlying genetic neurologic disorders, particularly monogenic conditions, is paramount for developing tailored therapies. When multiple disease-modifying therapies are available, early genetic diagnosis is crucial for appropriate therapy selection, highlighting the importance of early identification and intervention. A combination of drugs, each targeting unique genetic pathomechanisms, may provide additional clinical benefits.